REDESCRIPTION OF CUCULLANUS THERAPONI RASHEED, 1968 FROM NEW HOST FISH ARIODES DUSSUMIERI FROM KAKINADA, INDIA - LAKSHMI, B. BHARATHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Cucullanus theraponi, Rasheed, 1968 obtained from the intestine of marine fish Aridoes dussumieri fiom Kakinada is redescribed and figured. A dussumieri representes new host and new locality record. The present specimens tally with the principle characters of Cucullanus theraponi Rasheed, 1968. A detailed examination allowed us to consider the present specimens as C. theraponi, Rasheed, 1968 albeit certain variations.